Review Article: Potential of Rice (Oryza sativa L.) as Renewable Biomass Energy in The Agricultural Sector - Nio, Song Ai; Ludong, Daniel Peter Mantilen (JURNAL BIOS LOGOS, 2025)
The decline in fossil fuels, combined with increased fuel consumption and its negative effects on the environment, has necessitated the search for renewable energy alternatives. Among renewable energy sources, biomass is a dependable source because it is constantly available in nature. Indonesia has approximately 49,810 MW of potential plant-based biomass resources. The abundant availability of agricultural waste and biomass conversion techniques allow agricultural biomass, including rice, to be converted into an important renewable energy source. Investments in renewable energy derived from biomass can be made if supplies remain abundant and consistent in the future. Rice husks and straw, which are the primary waste products of rice production, have recently received a lot of attention as a renewable energy resource. The cost of rice husks and straw is lower and has no impact on food prices, and there is no conflict between food and fuel. This paper examines renewable energy derived from agricultural biomass, rice plant waste as a renewable energy source, and the conversion of rice plant waste into energy.